Critical analysis of the right of access electricity for the destitute in South Africa : issues and challenges - Moshoeu, Lesiba Benedict (My University, 2017)
This mini-dissertation examines and articulates the right to access electricity for the destitute in South Africa. Further, this mini-dissertation finds that high tariffs on electricity impede the accessibility and realisation of electricity as a human basic need. As a result, this mini- dissertation submits that accessibility and affordability of electricity as human basic need are compromised. Subsequently, the destitute are unable to afford and access electricity as encapsulated in the legislation. Therefore, this mini- dissertation submits that there must be investment in energy technologies to meet electricity demands. Furthermore, this mini-dissertation submits that there should be radical deployment of renewable energy in order to provide sufficient and affordable electricity to all, including the destitute. The investments in the building of the new power stations (Medupi, Kusile and Ingula) is welcomed by this mini- dissertation since it will solve the load shedding challenges which has affected South Africans and threaten the economic growth. Keywords: Energy, electricity, high tariffs, South Africa, destitute and accessibility.
Thesis (M. Dev.) -- University of Limpopo, 2017.
Keywords: Electricity; High teriffs; South Africa; Destitude and accessesibility; Energy technologies; Human rights; Electricity